Community physical activity: effects on functionality in chronic low back pain - Martins, Maicon da Silva (2017)
Objective: To evaluate the pain intensity, lumbar strength and functionality of individuals presenting chronic non-specific low back pain and taking part in a public physical exercise program. Methods: Exploratory, cross-sectional and quantitative survey conducted in 2017 with 130 women from 30 to 60 years of age and without history of spinal surgery. The Oswestry Low Back Pain Disability Questionnaire (ODQ) was applied for assessment of the disability related to the lumbar spine. The pain was quantified through the visual analog scale (VAS) and the lumbar muscle strength through lumbar dynamometry (Takei®). Results: Of the 130 participants, 97.7% (n=127) presented minimal functional disability related to the lumbar spine (ODQ). In respect to strength, 16.9% (n=10) presented normal values and 83.1% (n=120) were below the reference values, presenting muscle weakness. As for the pain intensity, 47.7% (n=67) of the participants showed mild intensity, 45.5% (n=59) presented moderate intensity and 6.9% (n=9), severe. Conclusion: The program has characteristics that contribute to maintaining under control the pain intensity, which has been slight, as well as the significant functional disability of the individuals. The muscle weakness in the lumbar region, presented by the participants without association with functionality, and the pain as well, might be factors that perpetuate the chronic low back pain. The findings suggest the need to revise the therapeutic prescription of the exercises of the implemented program.